Academic procrastination and exam anxiety in students from 3 to 5 of secondary level in schools in Lima - Querevalú Nabarro, Fernando (2020)
Objective: To determine the relationship between academic procrastination and anxiety in third, fourthand fifth year students at the secondary level. Methodology: Quantitative approach, non-experimentaldesign, cross-sectional and correlational in scope, since the variables were not manipulated, it wasmeasured at a certain time and it is sought to determine if there is a relationship between academicprocrastination and anxiety about exams. The instruments used were the Academic ProcrastinationScale (EPA) and the Self-Assessment Inventory of Exam Anxiety (IDASE). The sample consisted of280 students from two Adventist schools in Lima, who range between the ages of 14 and 17 of bothsexes. Results: There is a significant relationship between academic procrastination and test anxiety(rho = 0.118, p = 0.05), as well as in its dimension of postponement of activities and test anxiety (rho= 0.152 *, p = 0.011). Finally, it was found that the academic self-regulation dimension is not relatedto exam anxiety (rho = 0.091, p = 0.131). Conclusion: Therefore, there is a significant relationshipbetween academic procrastination and exam anxiety in high school students.